ANALISIS PEMANFAATAN SISTEM INFORMASI APLIKASI JKN MOBILE - Safitri Indah Paraswati; Sri Aminingsih; Ratna Indriati; Yovita Prabawati Tirta (CV Edujavare Publishing, 2025)
In 2017, the Social Security Administering Agency (BPJS) Health launched the JKN Mobile application to facilitate public access to various health services, including membership status checks, hospital searches, and online registration. This study aims to examine the relationship between information availability, suitability to needs, and information security with the utilization of the JKN Mobile application information system in Gedangan Village. The research employs a quantitative correlation design with a cross-sectional approach, involving 6,418 residents, from which 377 were selected using cluster sampling. Data were collected through questionnaires and analyzed using the chi-square test and multiple logistic regression. The results show a significant relationship between all independent variables and the utilization of the JKN Mobile application (p-value = 0.000), with information security being the most influential factor, as indicated by an Exp(B) value of 8.386. In conclusion, information availability, suitability to needs, and information security significantly influence the utilization of the JKN Mobile application, with information security increasing its utilization likelihood by 8.386 times.